2019
DOI: 10.1038/s41467-019-11226-5
|View full text |Cite
|
Sign up to set email alerts
|

Methylation analysis of plasma DNA informs etiologies of Epstein-Barr virus-associated diseases

Abstract: Epstein-Barr virus (EBV) is associated with a number of diseases, including malignancies. Currently, it is not known whether patients with different EBV-associated diseases have different methylation profiles of circulating EBV DNA. Through whole-genome methylation analysis of plasma samples from patients with nasopharyngeal carcinoma (NPC), EBV-associated lymphoma and infectious mononucleosis, we demonstrate that EBV DNA methylation profiles exhibit a disease-associated pattern. This observation implies a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 40 publications
(46 reference statements)
1
39
0
Order By: Relevance
“…107 Although EBVinduced DNA methylation is not documented in MS patients, it has been recognized in several other diseases, such as nasopharyngeal carcinoma, Hodgkin lymphoma, Burkitt lymphoma, and gastric carcinoma. [267][268][269][270][271][272] miRNAs signatures in MS patients may be defined by the environment and genetics. However, data from diverse groups, ethnicities, and countries need to be consolidated and reproduced to be accepted as robust.…”
Section: Resultsmentioning
confidence: 99%
“…107 Although EBVinduced DNA methylation is not documented in MS patients, it has been recognized in several other diseases, such as nasopharyngeal carcinoma, Hodgkin lymphoma, Burkitt lymphoma, and gastric carcinoma. [267][268][269][270][271][272] miRNAs signatures in MS patients may be defined by the environment and genetics. However, data from diverse groups, ethnicities, and countries need to be consolidated and reproduced to be accepted as robust.…”
Section: Resultsmentioning
confidence: 99%
“…Through this analysis, we have established that approximately 6% of the CpG sites covered by the Methylatio-nEPIC array provided significantly different p-values between gDNA and clDNA based on their methylation beta values. We have not addressed potential causes of the observed differences in methylation [20]. This may be due to the method through which the cell-line transformation occurs [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of the CpG island of promoter region results in the silence of tumor suppressor genes, and this feature is a characteristic abnormality seen in EBVassociated cancers [58][59][60]. Using a viral-wide genome approach, Lam et al [61] found distinct EBV DNA methy-lation profiles among different EBV-associated diseases; and by analyzing methylated DNA sequences allowed differentiation between NPC and non-NPC subjects. Aberrant methylation of tumor suppressor genes such as cadherin 4 (CDH4), cyclin-dependent kinase inhibitor 2A (CDKN2A/p16), and RAS association domain family protein 1A (RASSF1A) are early events in NPC tumorigenesis [62][63][64].…”
Section: Other Emerging Ebv Detection Markersmentioning
confidence: 99%
“…Mechanistically, epigenetic changes occur early in NPC and are readily detectable by hypermethylation panels; in locally advanced cases, the increased tumor burden is better detected via plasma EBV DNA assays. Furthermore, through whole-genome methylation analysis, Lam et al [61] demonstrated that methylation profiles exhibit a disease-associated pattern which differs for NPC, lymphoma, and infectious mononucleosis. By combining the differential methylation patterns with EBV DNA size and quantity, the study demonstrated an increased PPV of 35.1% in population screening of NPC, as compared to a PPV of 11.2% using only the conventional count-based plasma EBV DNA detection method [61].…”
Section: Sensitivity and Specificity Of Various Ebv Detection Techniquesmentioning
confidence: 99%